Visuospatial Attention Allocation as an Indicator of Cognitive Deficit in Traumatic Brain Injury: A Systematic Review and Meta-Analysis - Walz, Jacinta A.; Mani, Revathy; Alnawmasi, Mohammed M.; Khuu, Sieu K. (Frontiers in Human Neuroscience, 2021)
Traumatic Brain Injury (TBI) is defined by changes in brain function resulting from external forces acting on the brain and is typically characterised by a host of physiological and functional changes such as cognitive deficits including attention problems. In the present study, we focussed on the effect of TBI on the ability to allocate attention in vision (i.e., the use of endogenous and exogenous visual cues) by systematically reviewing previous literature on the topic. We conducted quantitative synthesis of 16 selected studies of visual attention following TBI, calculating 80 effect size estimates. The combined effect size was large (g =0.79, p <0.0001) with medium heterogeneity (I2 =68.39%). Subgroup analyses revealed an increase in deficit with moderate-to-severe and severe TBI as compared to mild TBI (F(2,76) =24.14, p <0.0001). Task type was another key source of variability and subgroup analyses indicated that higher order attention processes were severely affected by TBI (F(2,77) =5.66, p =0.0051). Meta-regression analyses revealed significant improvement in visual attention deficit with time (p(mild) =0.031, p(moderate-to-severe) =0.002, p(severe) <0.0001). Taken together, these results demonstrate that visual attention is affected by TBI and that regular assessment of visual attention, using a systematic attention allocation task, may provide a useful clinical measure of cognitive impairment and change after TBI.